Sportsmanship Behaviors in Early Adolescence and Gender and Family Attitudes - Sedat Özcan; Mehmet Fatih Eröz; Tahir Kılıç (Türk Spor ve Egzersiz Dergisi)
Introduction and Aim: Sportsmanship is a concept defined as the awareness of having the values required by sports and the golden key of sportive activities. In addition to changes in early adolescence, family attitude and gender are thought to be among the concepts affecting sportsmanship. This study aimed to examine sportsmanship behaviors and family attitude and gender characteristics. Materials and Methods: The study group consisted of a total of 300 students with a mean age of 12.48±.79, randomly selected from second-level primary schools in Isparta province. In the research conducted with a survey design, the "Physical Education Course Sportsmanship Behavior Scale (PECSBS)" developed by Koç (15) and the personal information form were used as data collection tools. In the data analysis, frequency, percentage, arithmetic mean, and standard deviation were used as descriptive statistical methods for personal information. Since the data were normally distributed, the t-test was used for paired groups, and the ANOVA test was used for multiple comparisons. Findings: According to the findings, the students’ sportsmanship behaviors were at a high level. According to gender, a statistically significant difference was found in favor of female students in the sub-dimensions of displaying appropriate behavior and avoiding inappropriate behavior and in the overall scale. According to the family attitudes of the students, there was no statistically significant difference in the sub-dimension of displaying appropriate behavior. However, in the sub-dimension of avoiding inappropriate behavior and in the overall scale, the scores of the students with democratic family attitudes were found to be higher than the scores of the children of families with liberal attitudes. Conclusion: When the sportsmanship behavior scores of second-level primary school students were examined, it was seen that female students scored higher than male students. It is thought that changing family attitudes will improve the sportsmanship behaviors of society.